A method for preparing a high-performance dual-phase magnesium-lithium alloy ring member
Patent Information
- Application Number
- CN202311838814.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-28
AI Technical Summary
然而,该类技术应用与镁锂合金环件存在以下问题:大型环件采用变温或低温变形工艺性较差,容易出现温度不均匀,引起内应力集中,从而出现各种缺陷;研究表明,双相镁锂合金时效过程中,β-Li的时效软化和α-Mg时效硬化存在竞争关系,高锂含量的镁锂合金在长时间时效热处理之后,易发生过时效软化;CN1165749861提供了一种双相镁锂合金强塑协同提高的复合变形工艺,采用了多道次变温混合轧制+时效处理相结合的工艺,获得高性能镁锂合金轧板,然而该工艺实际操作控温难度较大,不适用于大尺寸环形件生产
[0027] (1) The alloying element content of the ingot of the present invention involves the presence of two matrix phases, α-Mg and β-Li, in the magnesium-lithium alloy, which has a more balanced "strength-plasticity-density" performance compared with single-phase α-Mg or single-phase β-Li alloys. Al and Zn are the main strengthening elements, and the addition of RE can refine the as-cast structure and improve the comprehensive mechanical properties.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates generally to the field of magnesium-lithium alloy ring manufacturing technology, and specifically to a method for preparing a high-performance dual-phase magnesium-lithium alloy ring. Background Technology
[0002] Ultralight magnesium-lithium alloys are currently the lightest metallic structural materials used in engineering applications, with a density ranging from 1.35 to 1.65 g / cm³. 3 Compared to traditional magnesium alloys, these materials are 1 / 4 to 1 / 3 lighter. Magnesium-lithium alloys possess advantages such as low density, high specific stiffness, high specific strength, low anisotropy, good vibration resistance, and excellent plasticity, making them promising for applications in high-end fields such as aerospace and defense equipment. Ring-shaped components are typical aerospace parts. Addressing the urgent need for lightweight equipment, developing high-performance magnesium-lithium alloys to fabricate ring-shaped components can effectively reduce structural weight, decrease energy consumption, and promote equipment performance. However, the low absolute strength and difficulty in synergistically optimizing strength and plasticity of magnesium-lithium alloys limit their application in critical areas, and current research on the fabrication of high-performance magnesium-lithium alloy ring-shaped components is limited.
[0003] In engineering, the fabrication of magnesium-lithium alloy rings often draws on the traditional magnesium alloy ring rolling process, which involves hot ring rolling followed by aging heat treatment to achieve forming and strengthening. However, this method suffers from limited strengthening effect and low production efficiency, making it challenging to stably produce magnesium-lithium alloy rings with tensile strength >250MPa and elongation >20%. Existing research on the fabrication of magnesium-lithium alloy rings is limited.
[0004] For the fabrication of general magnesium alloy rings, production efficiency is typically improved by optimizing the plastic forming process. For example, CN103736888A discloses a forging method for magnesium alloy rings, employing die forging to achieve the final ring shape, which can be completed on a single hydraulic press, avoiding the need for relocation between workstations. CN113680933A discloses a forming method for thin-walled magnesium alloy rings, disclosing the use of resistance coil tooling design to create conditions for online heating of the magnesium alloy, reducing the time and cost of transfer and intermediate heat treatment. CN113635000A discloses a combined extrusion and rolling forming method for magnesium alloy rings, disclosing the use of reverse extrusion + grinding wheel to prepare hollow blanks, saving intermediate machining processes. However, research on improving the efficiency of heat treatment after deformation is lacking.
[0005] Optimizing the synergistic effect of strength and plasticity in magnesium-lithium alloys is challenging. A common strengthening technique for magnesium alloys is "high-temperature short-time solution treatment + medium / low-temperature deformation + low-temperature long-time aging." The principle is to reduce the final deformation temperature to preserve as much fine-grained structure as possible, and combine this with solution-aging heat treatment to promote the formation of precipitated phases, resulting in a second-phase strengthening effect. For example, CN116574986A discloses a composite deformation process for synergistically improving the strength and plasticity of dual-phase magnesium-lithium alloys. It proposes using "homogenization + high-temperature short-time solution treatment" of the ingot before deformation, combined with variable-temperature multi-pass deformation and low-temperature long-time aging to achieve synergistic optimization of strength and plasticity. However, the application of this technology to magnesium-lithium alloy rings has the following problems: large rings have poor processability when using variable-temperature or low-temperature deformation, and are prone to temperature inhomogeneity, causing internal stress concentration and various defects; research shows that during the aging process of dual-phase magnesium-lithium alloys, the aging softening of β-Li and the aging hardening of α-Mg are competitive, and magnesium-lithium alloys with high lithium content are prone to over-aging softening after long-term aging heat treatment; CN1165749861 provides a composite deformation process that synergistically improves the strength and plasticity of dual-phase magnesium-lithium alloys, which adopts a process combining multi-pass variable-temperature mixed rolling and aging treatment to obtain high-performance magnesium-lithium alloy rolled plates. However, the actual operation of this process is difficult to control the temperature, and it is not suitable for the production of large-size rings. Summary of the Invention
[0006] This invention proposes a method for preparing high-performance biphase magnesium-lithium alloy ring parts. This production method is suitable for preparing high-lithium-content, low-density biphase magnesium-lithium alloys, which can improve production efficiency and achieve synergistic optimization of strength and plasticity in magnesium-lithium alloys.
[0007] The technical solution of this invention is: a method for preparing a high-performance dual-phase magnesium-lithium alloy ring, comprising the following steps:
[0008] Step 1: Ingot preparation: Magnesium-lithium alloy is vacuum-cast and machined to obtain an ingot; the alloying elements in the magnesium-lithium alloy include Li, Al, Zn and rare earth elements, and the ingot contains α-Mg phase and β-Li phase;
[0009] Step 2: Homogenization treatment;
[0010] Step 3: Multi-directional forging of the billet, including punching;
[0011] Step 4: Ring forming:
[0012] Step 5: Quenching in warm water;
[0013] The fifth step, warm water quenching, refers to: using warm water spray to cool the workpiece after the treatment in the fourth step; after the surface temperature of the workpiece drops to below 150°C, it is directly immersed in a warm water pool or the surface of the workpiece is rinsed with warm water. After the temperature drops to below 65°C, the surface moisture is wiped dry and air-dried; the temperature of the warm water is 45-95°C.
[0014] Furthermore, in step one above: the alloying elements in the magnesium-lithium alloy include the following composition by mass percentage: Li: 7.0-11.0%, Al: 2.0-5.0%, Zn: 0.5-2%, rare earth metals: 0.1-3%, and rare earth elements include one or more of Gd, Y, Er, and Nd.
[0015] Furthermore, the homogenization treatment in step two above refers to: placing the ingot at 300-400℃ for 4-12 hours.
[0016] Furthermore, step three above includes the following steps:
[0017] S1, Free forging blank;
[0018] S2, punching;
[0019] After the homogenization process in step two is completed, the ingot is directly subjected to free forging in step three. That is, the ingot is not subjected to cooling or heat treatment between the homogenization process in step two and the free forging in step three.
[0020] Furthermore, the free forging process parameters in step S1 are: deformation temperature 280-380℃, anvil temperature 200-300℃, 1-3 reversals during free forging, deformation amount in each direction 20-80% during each reversal, and final rounding, axial upsetting and shaping.
[0021] Furthermore, the punching process in step S2 is as follows: the billet after upsetting in step S1 is placed on a flat anvil, and the billet temperature is not lower than 200°C; the punch is pressed down, pressing down at least 60% in the height direction; the billet is flipped over, the punch is pressed down again, and the blank is punched out; the end face of the billet is flattened.
[0022] Furthermore, the specific forging operation of the free forging blank in step S1 above is as follows: first, the ingot is axially upset, then shaped and forged into a square, then drawn out perpendicular to the original axis of the ingot, and finally upset and shaped in the reverse direction along the drawing direction.
[0023] Furthermore, the ring forming in step four above adopts a forging and reaming process, specifically: forging temperature 250-350℃, single-pass deformation amount 10-30%.
[0024] Furthermore, in step four above, after the forging and reaming of the frame, a hot ring rolling process is also included. The hot ring rolling process parameters are: workpiece temperature 250-350℃, drive roll, core roll, clamping roll and tapered roll preheated to 250-350℃, and rolling speed 1000-1500mm / s.
[0025] Furthermore, in step five above, the temperature of the warm water is 65–85°C.
[0026] The beneficial effects of this invention are as follows:
[0027] (1) The alloying element content of the ingot of the present invention involves the presence of two matrix phases, α-Mg and β-Li, in the magnesium-lithium alloy, which has a more balanced "strength-plasticity-density" performance compared with single-phase α-Mg or single-phase β-Li alloys. Al and Zn are the main strengthening elements, and the addition of RE can refine the as-cast structure and improve the comprehensive mechanical properties.
[0028] (2) The ingot homogenization process of the present invention re-dissolves dendritic segregation into the matrix, thereby improving the homogenization of the microstructure and properties. At the same time, since the ingot homogenization process is carried out directly without cooling, the ingot homogenization process is also used as a preheating process before the billet is opened.
[0029] (3) The purpose of free forging is to further homogenize the microstructure and reduce anisotropy. Magnesium-lithium alloy has a wide plastic deformation process window and is not easy to crack during forging. The designed reversal number and deformation amount are conducive to improving the grain refinement and uniformity of the billet. In the punching process, the piercing is not carried out by mechanical processing. The bidirectional punching method of flipping the billet can save mechanical wear and can be completed on the same hydraulic press, reducing the cost of workpiece transfer and reheating.
[0030] (4) The forging and reaming process for ring forming is a highly flexible forging process that can forge rings of different sizes without requiring complex mold design. For larger rings with thinner walls, hot ring rolling can be used after forging and reaming, which improves the efficiency and flexibility of forming. This invention improves the production efficiency of the forging stage by saving heat homogenization and replacing mechanical piercing with punching blanking.
[0031] (5) The warm water quenching process of this invention differs from that of traditional magnesium alloys. Solid solution strengthening has a high influence on the strengthening of magnesium-lithium alloys. For magnesium-lithium alloys with high Li content, high-temperature aging treatment easily induces aging softening, while low-temperature long-term aging treatment affects production efficiency. Moreover, too many second phases precipitate after aging, which are very likely to transform and coarsen during subsequent service, resulting in potential performance degradation. This invention adopts an appropriate increase in deformation temperature and uses warm water quenching to control a reasonable cooling rate: on the one hand, it reduces deformation resistance, optimizes formability, and improves forming efficiency; on the other hand, compared with cold water quenching, warm water quenching can prevent severe deformation caused by internal stress concentration, and prevent the material from becoming excessively brittle. Compared with air cooling, the strengthening effect is better, and it can optimize strength and plasticity in a coordinated manner.
[0032] This invention eliminates the post-forming aging heat treatment process for ring parts, minimizing intermediate heat treatment steps and addressing the issues of long aging heat treatment times and high labor and energy costs associated with workpiece heat treatment transport. It employs a "high-temperature hot deformation + warm water quenching" approach for ring forming, enhancing the solid solution strengthening level of the magnesium-lithium alloy workpiece while preserving the deformed microstructure. By eliminating the post-deformation aging heat treatment step and utilizing the characteristics of magnesium-lithium alloys, solid solution strengthening is the primary strengthening method, reducing the transport and energy costs associated with aging heat treatment of large workpieces, improving production efficiency, and achieving synergistic optimization of strength and plasticity. In industrial production of magnesium-lithium alloy ring parts, it consistently achieves mechanical properties with a tensile strength >250MPa and an elongation >20%. Detailed Implementation
[0033] Example 1:
[0034] A method for preparing a high-performance dual-phase magnesium-lithium alloy ring-shaped component includes the following steps:
[0035] The mass percentage composition of the main alloying elements in the magnesium-lithium alloy is as follows: Li: 9.0–10.5%, Al: 2.5–3.5%, Zn: 0.5–1.0%, Gd: 0.5–1.5%. The magnesium-lithium alloy is vacuum-cast and machined to obtain a cast rod with a diameter of Φ300 mm and a length of 500 mm.
[0036] Homogenization treatment is carried out by keeping the temperature at 320-340℃ for 5-8 hours.
[0037] Preheat the anvil to 320-340℃ and perform free forging: slowly upset along a height of 500mm to a height of about 280mm and an outer diameter of about Φ(430±10)mm; flatten along a diameter of Φ430mm, slightly forge into a square shape, and then draw it out in a different direction to about Φ300mm×500mm; slowly upset along a height of 500mm to a height of about 240±10mm and an outer diameter of about Φ460mm; punch a hole of Φ160-180mm in the center of the Φ460mm diameter blank;
[0038] The frame is pre-forged and expanded to a diameter of approximately 600mm (outer diameter), 430mm (inner diameter), and 230mm (height) using a step-by-step process; then rolled into a ring to a diameter of 810mm (inner diameter), 690mm (inner diameter), and 230mm (height).
[0039] Then immediately spray with warm water at 70±5℃, wipe dry and air dry. The room temperature tensile strength, yield strength and elongation of the magnesium-lithium alloy are shown in Table 1.
[0040] Example 2:
[0041] A method for preparing a high-performance dual-phase magnesium-lithium alloy ring-shaped component includes the following steps:
[0042] The mass percentage composition of the main alloying elements in the magnesium-lithium alloy is as follows: Li: 9.0–10.5%, Al: 2.5–3.5%, Zn: 0.5–1.0%, (Gd+Y): 0.5–1.5%. The magnesium-lithium alloy is vacuum-cast and machined to obtain a cast ingot with a diameter of Φ300 mm and a length of 420 mm.
[0043] Homogenization treatment is carried out by keeping the temperature at 320-340℃ for 5-8 hours.
[0044] Preheat the anvil to 320-340℃ and perform free forging: slowly upset along the 420mm height direction to a height of about 280mm and an outer diameter of about Φ(400±10)mm; flatten along the Φ400mm diameter direction, slightly forge into a square shape, and then draw it out in the opposite direction to about Φ280mm×480mm; slowly upset along the 480mm height direction to a height of about 240±10mm and an outer diameter of about Φ440mm; punch a Φ160-180mm hole in the center of the Φ440mm diameter blank;
[0045] The frame is pre-forged and enlarged step by step, and the end face is flattened to a size of approximately outer diameter Φ810mm, inner diameter Φ710mm, and height 230mm, and then flattened and shaped.
[0046] Then, immediately spray with warm water at 55±5℃, wipe dry, and air dry. The room temperature tensile strength, yield strength, and elongation of this magnesium-lithium alloy are shown in Table 1.
[0047] Comparative Example 1:
[0048] A method for preparing a magnesium-lithium alloy ring includes the following steps:
[0049] The mass percentage composition of the main alloying elements in the magnesium-lithium alloy is as follows: Li: 9.0–10.5%, Al: 2.5–3.5%, Zn: 0.5–1.0%, Gd: 0.5–1.5%. The magnesium-lithium alloy is vacuum-cast and machined to obtain a cast rod with a diameter of Φ300 mm and a length of 500 mm.
[0050] Homogenization treatment is carried out by keeping the temperature at 320-340℃ for 5-8 hours.
[0051] Preheat the anvil to 280-320℃ and perform free forging: slowly upset along a height of 500mm to a height of about 280mm and an outer diameter of about Φ(430±10)mm; flatten along a diameter of Φ430mm, slightly forge into a square shape, and then draw it out to about Φ300mm×500mm; slowly upset along a height of 500mm to a height of about 240±10mm and an outer diameter of about Φ460mm; punch a hole of Φ160-180mm in the center of the Φ460mm diameter blank;
[0052] The workpiece was pre-forged using a frame, with the hole enlarged and the end face flattened to approximately an outer diameter of Φ600mm, an inner diameter of Φ430mm, and a height of 230mm. It was then rolled into a ring to a size of Φ810mm, an inner diameter of Φ690mm, and a height of 230mm, followed by air cooling. The workpiece underwent aging heat treatment at 220–240℃ for 2–4 hours, and was then air-cooled. The room temperature tensile strength, yield strength, and elongation of this magnesium-lithium alloy are shown in Table 1.
[0053] Comparative Example 2:
[0054] A method for preparing a magnesium-lithium alloy ring includes the following steps:
[0055] The mass percentage composition of the main alloying elements in the magnesium-lithium alloy is as follows: Li: 9.0–10.5%, Al: 2.5–3.5%, Zn: 0.5–1.0%, (Gd+Y): 0.5–1.5%. The magnesium-lithium alloy is vacuum-cast and machined to obtain a cast ingot with a diameter of Φ300 mm and a length of 420 mm.
[0056] Homogenization treatment is carried out by keeping the temperature at 320-340℃ for 5-8 hours.
[0057] Preheat the anvil to 280-320℃ and perform free forging: slowly upset along the 420mm height direction to a height of about 280mm and an outer diameter of about Φ(400±10)mm; flatten along the Φ400mm diameter direction, slightly forge into a square shape, and then draw it out in the opposite direction to about Φ280mm×480mm; slowly upset along the 480mm height direction to a height of about 240±10mm and an outer diameter of about Φ440mm; punch a Φ160-180mm hole in the center of the Φ440mm diameter blank;
[0058] The workpiece was pre-forged and enlarged using a frame, with the end face flattened to approximately 810mm outer diameter, 710mm inner diameter, and 230mm height, achieving a smooth and well-shaped surface. The workpiece underwent aging heat treatment at 220–240℃ for 2–4 hours, followed by air cooling. The room temperature tensile strength, yield strength, and elongation of this magnesium-lithium alloy are shown in Table 1.
[0059] Table 1 Mechanical properties of magnesium-lithium alloy rings obtained in the examples / comparative examples
[0060] Example 1 271 219 26.0 Example 2 260 215 25.0 Comparative Example 1 232 200 20.0 Comparative Example 2 220 177 20.5
[0061] This invention simultaneously studied the effects of different quenching temperatures on the material properties of the magnesium-lithium alloy ring product of this invention. After deformation, the small samples were quenched (sample temperature 250-350℃, the preparation process before quenching was the same), and after water quenching at different temperatures, samples were taken and tested. The performance comparison is shown in Table 2 below.
[0062] Table 2 Comparison of material properties obtained by quenching at different water temperatures
[0063]
[0064] It is known that cold water quenching results in high strength but extremely low elongation; increasing the quenching temperature can effectively improve the embrittlement phenomenon, and compared with the homogenized state, both strength and plasticity are improved.
[0065] This invention simultaneously studied the impact of the free forging + ring rolling process on the performance of the obtained products compared with the commonly used casting + homogenization process in the prior art. Under the premise that other preparation processes are the same, the mechanical properties of the products obtained by the free forging + ring rolling process and the casting + homogenization process are compared as shown in Table 3 below.
[0066] Table 3 Comparison of material properties obtained by free forging + ring rolling process and cast + homogenization process
[0067]
[0068] It can be seen that the free forging + ring rolling process can significantly improve the plasticity of materials and optimize the uniformity of strength.
[0069] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing a high-performance dual-phase magnesium-lithium alloy ring component, characterized in that, Includes the following steps: Step 1: Ingot preparation: Magnesium-lithium alloy is vacuum-cast and machined to obtain an ingot; the alloying elements in the magnesium-lithium alloy include Li, Al, Zn and rare earth elements, and the ingot contains α-Mg phase and β-Li phase; The alloying elements in the magnesium-lithium alloy include the following composition by mass percentage: Li: 7.0-11.0%, Al: 2.0-5.0%, Zn: 0.5-2%, rare earth metals: 0.1-3%, and rare earth elements include one or more of Gd, Y, Er, and Nd; Step 2: Homogenization treatment. Place the ingot at 300-400℃ and keep it at that temperature for 4-12 hours. Step 3: Multi-directional forging billet; Step three includes the following steps: S1, Free forging blank; The free forging process parameters in step S1 are: deformation temperature 280~380℃, anvil temperature 200~300℃, 1~3 reversals during free forging, deformation amount in each direction 20~80% during a single reversal, and final rounding, axial upsetting and shaping. S2, punching; The punching process in step S2 is as follows: the billet after upsetting in step S1 is placed on a flat anvil, and the billet temperature is not lower than 200°C; the punch is pressed down, pressing down at least 60% in the height direction; the billet is flipped over, the punch is pressed down again, and the blank is punched out; the end face of the billet is flattened. After the homogenization process in step two is completed, the ingot is directly subjected to free forging in step three. That is, the ingot is not subjected to cooling or heat treatment between the homogenization process in step two and the free forging in step three. Step 4: Ring forming; The ring forming in step four is carried out by forging and reaming using a forging frame. The specific process is as follows: forging temperature 250~350℃, single-pass deformation amount 10~30%; In step four, after the forging and reaming of the frame, a hot ring rolling process is also included. The hot ring rolling process parameters are: workpiece temperature 250-350℃, drive roll, core roll, clamping roll and tapered roll preheated to 250-350℃, rolling speed 1000-1500mm / s. Step 5: Quenching in warm water; The fifth step, warm water quenching, refers to: cooling the workpiece after the treatment in the fourth step by spraying it with warm water; after the surface temperature of the workpiece drops to below 150°C, it is directly immersed in a warm water pool or the surface of the workpiece is rinsed with warm water. After the temperature drops to below 65°C, the surface moisture is wiped dry and air-dried; the temperature of the warm water is 45~95°C. The aging heat treatment process after ring forming is eliminated.
2. The method for preparing a high-performance dual-phase magnesium-lithium alloy ring according to claim 1, characterized in that, The specific forging operation of the free forging blank in step S1 is as follows: first, the ingot is upset axially, then shaped and forged into a square, then drawn out perpendicular to the original axial direction of the ingot, and finally upset and shaped in the reverse direction along the drawing direction.
3. The method for preparing the high-performance dual-phase magnesium-lithium alloy ring according to claim 1, characterized in that, In step five, the temperature of the warm water is 65~85℃.
Citation Information
Patent Citations
Forging forming method for magnesium alloy rings
CN103736888A
Extrusion-rolling composite forming method for magnesium alloy ring piece
CN113635000A
Forming method of thin-wall magnesium alloy ring piece
CN113680933A
Composite deformation process for synergistically improving strength and plasticity of double-phase magnesium-lithium alloy
CN116574986A
High-strength aluminum-magnesium-lithium alloy and preparation method thereof
CN112853181A